Pengaruh Skeptisme Profesional, Situasi Audit, Kompetensi, Etika Audit, Pengalaman dan Keahlian Audit Terhadap Ketepatan dalam Pemberian Opini oleh Auditor BPK - Surfeliya, Fanny; ', Andreas; ', Yusralaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is a research that analyzes the factors that influence the decision to give an audit opinion. The focus of this study analyzed the relationship of professional skepticism, audit situation, competention , ethics, experience and expertise, with the decision to give an audit opinion by the auditor. The purpose of this study was to analyze and obtain empirical evidence on the relationship of professional skepticism in auditing, audit situation,interest, ethics, experience and expertise, make an audit of to accuracy of auditor opinion. Data collecting in this research use kuesioner to 40 laboring auditor at Badan Pemerikasaan Keuangan of Riau in Pekanbaru. Technique in intake of sample is sampling purposive and used by analyzer is doubled regresi. Result from this research is auditor professional skeptisisme have an effect on signifikan to accuracy giving of auditor opinion. And situation audit, competention, ethics, and experience and expertise of audit do not have an effect on signifikan to accuracy giving of auditor opinion.Keywords : professional skeptisisme, audit situation, competention, ethics, experience and expertise, make an audit of to accuracy of opinion auditor.